2019
DOI: 10.1371/journal.pone.0215988
|View full text |Cite
|
Sign up to set email alerts
|

Shrubs indirectly increase desert seedbanks through facilitation of the plant community

Abstract: The mechanisms supporting positive ecological interactions are important. Foundation species can structure desert biodiversity by facilitating seedbanks of annual plants, but the direct and indirect mechanisms of shrub effects on seedbank have not been experimentally decoupled. We conducted the first test of shrubs increasing seedbank densities through direct effects on the seedbank (i.e. shrub seed-trapping, animal-mediated dispersal) and indirect effects by facilitating the annual plant community (i.e. seed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 67 publications
0
15
0
1
Order By: Relevance
“…Previous studies showed that the size of a shrub could impact the arrival of other plant seeds (Pugnaire & Lázaro, 2000) because larger shrub canopy surfaces can provide greater facilitative effects on plants. Shrubs with higher canopy surface and taller can intercept more solar radiation (Maestre & Cortina, 2005), have higher soil nutrients (Zhang, Yang, Wang, & Zhao, 2015), or lower evapotranspiration (Kidron & Gutschick, 2013) creating a favorable microclimate for seed production, particularly by annuals (Filazzola et al, 2019). As a result, compared to the other shrubs, taller and larger canopy in A. scoparia might increase SSB density through higher seed production by other plants.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that the size of a shrub could impact the arrival of other plant seeds (Pugnaire & Lázaro, 2000) because larger shrub canopy surfaces can provide greater facilitative effects on plants. Shrubs with higher canopy surface and taller can intercept more solar radiation (Maestre & Cortina, 2005), have higher soil nutrients (Zhang, Yang, Wang, & Zhao, 2015), or lower evapotranspiration (Kidron & Gutschick, 2013) creating a favorable microclimate for seed production, particularly by annuals (Filazzola et al, 2019). As a result, compared to the other shrubs, taller and larger canopy in A. scoparia might increase SSB density through higher seed production by other plants.…”
Section: Discussionmentioning
confidence: 99%
“…For the soil bank treatment, on 16 November 2016, we collected 0.5 L of topsoil, including the litter on top, to a depth of 6 cm from each of 10 individual shrubs or trees in a parallel band 5 and 20 m from the segments. Soils under shrubs and trees, and the litter, foster high seed bank densities in arid environments (Guo et al 1998; Filazzola et al 2019). Seeds in arid environments are densest in the top 0–1 cm but can be unevenly distributed throughout a 10‐cm profile with smallest and largest seeds on the surface and medium to large seeds settling lower in the profile (Guo et al 1998).…”
Section: Methodsmentioning
confidence: 99%
“…Increased competition within understories likely acts as a mechanism promoting two‐phase vegetation mosaics (i.e. understorey and open microsites), because these microsites can sometimes regulate or filter the emergence of dominant plants via the classical direct effects of nurse plants, but also via indirect effects mediated by neighbourhoods, in combination with other spatiotemporally variable mechanisms such as seed trapping or rainfall (Giladi et al, 2013; Cipriotti et al, 2014; Cipriotti & Aguiar, 2015; Filazzola et al, 2019). Importantly, understorey microsites in stressful environments can open doors to invasions through facilitation and biotic acceptance (Flory & Bauer, 2014; Badano et al, 2015; Lucero et al, 2019), which have the potential to compete and negatively impact the facilitator species (Rodríguez‐Buriticá & Miriti, 2009; Filazzola et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Increased competition within understories likely acts as a mechanism promoting two-phase vegetation mosaics (i.e. understorey and open microsites), because these microsites can sometimes regulate or filter the emergence of dominant plants via the classical direct effects of nurse plants, but also via indirect effects mediated by neighbourhoods, in combination with other spatiotemporally variable mechanisms such as seed trapping or rainfall (Giladi et al, 2013;Cipriotti et al, 2014;Cipriotti & Aguiar, 2015;Filazzola et al, 2019).…”
Section: Plantago Limensis Fuertesimalva Peruviana P Lantago Limensis Fuertesimalva Peruvianamentioning
confidence: 99%